2017
DOI: 10.1590/1413-812320172212.07862016
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for chronic diseases in adults: a population-based study

Abstract: The article describes the relative frequency ok of risk and protective behaviors for chronic non-communicable diseases (NCDs) in adults residing in Viçosa, Brazil. A cross-section-al population-based study including 1,226 adults living in the municipality. We used a structured questionnaire containing questions sociodemographic and behavioral The risk and protection factors evaluated were: smoking, physical activity, excessive consumption of alcohol and food consumption. The proportion of risk and protection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The existing studies have demonstrated that the socioeconomic factors are closely related to the cause of mental disease, and the lower socioeconomic status is related to the worse results of psychological health [7]- [9] . According to Cristine et al, those people with lower socioeconomic status were more likely to live in a bad environment and have negative emotions such as sense of loss and depression [10] . Therefore, SES has a certain influence on individual depression.…”
Section: Introductionmentioning
confidence: 99%
“…The existing studies have demonstrated that the socioeconomic factors are closely related to the cause of mental disease, and the lower socioeconomic status is related to the worse results of psychological health [7]- [9] . According to Cristine et al, those people with lower socioeconomic status were more likely to live in a bad environment and have negative emotions such as sense of loss and depression [10] . Therefore, SES has a certain influence on individual depression.…”
Section: Introductionmentioning
confidence: 99%
“…Th ese factors increase the chance of skin ulcer occurring. (8,9) It is estimated that by 2050, about 25% of the elderly population will have chronic skin injuries. (10) Chronic skin ulcer are those whose etiologies are due to late diagnosis or inadequate treatment of longterm infectious or NCDs.…”
Section: Introductionmentioning
confidence: 99%